Protocol invariance and the timing of decisions in dynamic games - Ulrich Doraszelski; Juan F. Escobar (Theoretical Economics, 2019)
We characterize a class of dynamic stochastic games that we call separable dynamic games with noisy transitions and establish that these widely used models are protocol invariant provided that periods are sufficiently short. Protocol invariance means that the set of Markov perfect equilibria is nearly the same irrespective of the order in which players are assumed to move within a period. Protocol invariance can facilitate applied work and renders the implications and predictions of a model more robust. Our class of dynamic stochastic games includes investment games, R&D races, models of industry dynamics, dynamic public contribution games, asynchronously repeated games, and many other models from the extant literature.
Keywords: C7; C6; D0; 330; Dynamic stochastic games; timing of decisions; commitment; protocol invariance